Surgical Site Infections Are Associated With Higher Blood Loss and Open Access in General Thoracic Practice - Aeschbacher, Pauline; Nguyen, Thanh-Long; Dorn, Patrick; Kocher, Gregor Jan; Lutz, Jon Andri (Frontiers in Surgery, 2021)
Background: Surgical site infections (SSI) are the most costly and second most frequent healthcare-associated infections in the western world. They are responsible for higher postoperative mortality and morbidity rates and longer hospital stays. The aim of this study is to analyze which factors are associated with SSI in a modern general thoracic practice. Methods: Data were collected from our department’s quality database. Consecutive patients operated between January 2014 and December 2018 were included in this retrospective study. Results: 2430 procedures were included. SSI were reported in 37 cases (1.5%). The majority of operations were video-assisted (64.6%). We observed a shift towards video-assisted thoracic surgery in the subgroup of anatomical resections during the study period (2014: 26.7%, 2018: 69.3%). The multivariate regression analysis showed that blood loss >100ml (p=0.029, HR 2.70) and open surgery (p=0.032, HR 2.37) are independent risk factors for SSI. The latter was higher in open surgery than in video-assisted thoracic procedures (p<0.001). In the subgroup of anatomical resection, we found the same correlation (p=0.043). SSI are also associated with significantly longer mean hospital stays (17.7 vs. 7.8 days, p<0.001). Conclusion: As SSI represent higher postoperative morbidity and costs, efforts should be made to maintain their rate as low as possible. In terms of prevention of surgical site infections, video-assisted thoracic surgery should be favored over open surgery whenever possible as well a low blood loss.